The development and validation of an acculturation scale: An empirical study based on experimental data - J. Q. Zhu; H. Li (South African Journal of Business Management, 2016)
Based on a review of existing acculturation models, an adjusted acculturation model was proposed in this study and a scale for measuring an acquirer's acculturation strategy was developed. We designed an experiment to collect data to validate this scale. Using CR values, CITC and EFA, we examined the scale items, and using Cronbach's alpha and the AVE method, we tested the scale's reliability, convergent validity, and discriminant validity. Finally, taking resistance to change as a criterion, we tested the scale's criterion-related validity. The results show that the scale has good measurement properties.
Keywords: 650